Moderasi Beragama dalam Kearifan Lokal (Al-Wasatiyah: Journal of Religious Moderation, 2024)
This study emphasizes the importance of respecting localtraditions to achieve religious harmony by examining how the role oflocal traditions shapes harmony as an indicator of religiousmoderation. The form of this research is literature and includesqualitative research from books on religious moderation of theMinistry of Religious Affairs and periodicals such as researchjournals as data materials that are still related to the research topic.The results of the study indicate that local traditions have deepsignificance in the social context of Indonesia, acting as a glue forcultural identity, fostering harmony among diverse groups, andstrengthening a sense of togetherness among various ethnic andreligious groups. In strengthening harmony through tradition as anindicator of religious moderation, there are several approaches. First.Tolerance. Second. Respect for religious and cultural diversity. Third.Applying local traditional values. Fourth. Effective communication.Through these approaches, it is hoped that local traditions inIndonesia will not only reflect an extraordinary cultural richness butalso contribute to the formation of social identity and harmonyamong religions.